Phenolic compositions and antioxidant properties of leaves of eight persimmon varieties harvested in different periods. (15th August 2019) - Chang, Ya-Ling; Lin, Jau-Tien; Lin, Huey-Ling; Liao, Po-Lin; Wu, Po-Jen; Yang, Deng-Jye
Highlights: Phenolic compositions of the leaves from eight persimmon varieties are determined. Harvest time and variety of samples affect antioxidant components and activities. Temperature, solar radiation and sunshine duration affect phenolic contents in samples. Antioxidant activities of samples are significantly correlated with phenolic contents. Abstract: The compositions and contents of antioxidant components and antioxidant attributes (scavenging DPPH radicals, TEAC, ferric reducing power and inhibiting Cu 2+ -induced human LDL oxidation) for the leaves of eight persimmon varieties harvested from Sep. to Nov. were determined. Harvest time and variety were important factors affecting the compositions and contents of phenolic compounds in persimmon leaves; moreover, phenolic contents (polyphenol, flavonoid, condensed tannin and phenolic acid) of the leaves were significantly correlated with their antioxidant activities. For each variety, the leaves harvested in months with higher temperature, solar radiation and sunshine duration had higher phenolic contents contributing to better antioxidant properties (ranking: Sep. > Oct. > Nov.). In addition, the compositions and contents of phenolic components and antioxidant capacities for the leaves from various persimmon varieties were also different. The leaves of persimmon varieties belonging to pollination constant and astringent (PCA) had higher phenolic contents and also presented better antioxidant effects.